Protocol Adherence for Severe Sepsis and Septic Shock Management in the Emergency Department; a Clinical Audit - Alavi-Moghaddam, Mostafa; Anvari, Ali; Soltani Delgosha, Reaza; Kariman, Hamid (Archives of Academic Emergency Medicine, 2017)
Introduction: Although significant development in the field of medicine is achieved, sepsis is still a major issue threatening humans’ lives. This study was aimed to audit the management of severe sepsis and septic shock patients in emergency department (ED) according to the present standard guidelines. Method: This is a prospective audit on approaching adult septic patients who were admitted to ED. The audit checklist was created based on the protocols of Surviving Sepsis Campaign and British Royal College recommendations. The mean knowledge score and the compliance rate of studied measures regarding standard protocols were calculated using SPSS version 21. Results: 30 emergency medicine residents were audited (63.3% male). The mean knowledge score of studied residents regarding standard guidelines were 5.07 ± 1.78 (IQR = 2) in pre education and 8.17 ± 1.31 (IQR = 85) in post education phase (p < 0.001). There was excellent compliance with standard in 4 (22%) studied measures, good in 2 (11%), fair in 1 (6%), weak in 2 (11%), and poor in 9 (50%). 64% of poor compliance measures correlated to therapeutic factors. After training, score of 5 measures including checking vital signs in < 20 minute, central vein pressure measurement in < 1 hour, blood culture request, administration of vasopressor agents, and high flow O2 therapy were improved clinically, but not statistically. Conclusion: The protocol adherence in management of severe sepsis and septic shock for urine output measurement, central venous pressure monitoring, administration of inotrope agents, blood transfusion, intravenous antibiotic and hydration therapy, and high flow O2 delivery were disappointingly low. It seems training workshops and implementation of Clinical audit can improve residents’ adherence to current standard guidelines regarding severe sepsis and septic shock.